2021
DOI: 10.1007/s11270-021-04994-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Microplastics and Additives on the Health Status of Loggerhead Turtles (Caretta caretta) Stranded Along the Central Adriatic Coast

Abstract: Loggerhead sea turtle (C. caretta) is the official European bioindicator of marine litter in the Mediterranean Sea. In 2019, 8 sea turtles, out of 28 specimens loggerhead on the Adriatic coast of Molise, were subjected to necropsy. The intestinal contents were collected and the microplastics until 0.45 μm were extracted. Qualitative and quantitative assessments were performed by stereomicroscope observation and spectroscopic analyses (attenuated total reflection-Fourier transform infrared spectroscopy, ATR-FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Among all of the exploited techniques, Raman Microspectroscopy (RMS) can be considered the gold standard, since it lets researchers characterise not only the morphological features of microparticles but also their chemical composition in terms of both polymer matrices and pigments. Moreover, RMS presents the advantage of enabling the analysis of MPs as small as ~2 µm directly on filtration membranes, thanks to the high potential of light scattering [18][19][20]. Recently, our research group, for the first time, detected the presence of MPs in human placenta samples; this study, carried out by Raman Microspectroscopy, received extensive attention, since the delicate role played by this organ may be perturbed by the presence of MPs [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among all of the exploited techniques, Raman Microspectroscopy (RMS) can be considered the gold standard, since it lets researchers characterise not only the morphological features of microparticles but also their chemical composition in terms of both polymer matrices and pigments. Moreover, RMS presents the advantage of enabling the analysis of MPs as small as ~2 µm directly on filtration membranes, thanks to the high potential of light scattering [18][19][20]. Recently, our research group, for the first time, detected the presence of MPs in human placenta samples; this study, carried out by Raman Microspectroscopy, received extensive attention, since the delicate role played by this organ may be perturbed by the presence of MPs [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 100% of the short-beaked common dolphin (Delphinus delphis) found on the Galician Coast and examined by Hernandez-Gonzalez et al [87] were contaminated by MPs (12 ± 8 MPs/org). There has been one report of MPs in Mediterranean Sea turtles, with Di Renzo et al [60] reporting that 66% of Adriatic Sea loggerhead turtles (Caretta caretta) they investigated were contaminated by an average of 4.75 MPs/org. There has also only been one study of MPs in Mediterranean seabirds, with the highest levels of MPs observed in Northern Gannet (Morus bassanus, 49.3 ± 77.7 MPs/org [49]).…”
Section: Microplastics In Field Collected Biotamentioning
confidence: 99%
“…Yolk and embryo pools were digested in a pre-filtered 10% KOH solution (fiber-glass filter, 1.6 µm pore-size, Whatman GF/A) made with deionized water and KOH tablets (Sigma-Aldrich, Milan, Italy). MP extraction was performed following a modified version of the existing protocol described by Di Renzo et al (2021) [26] and summarized below. The solution was added to each sample (ratio 1:10 w/v) and incubated at 40 • C for 24 h. After 24 h, the digestates were filtered in fiber-glass filters (1.6 µm pore-size, Whatman GF/A, Merck KGaA, Darmstadt, Germany) using a vacuum pump connected to a filter funnel.…”
Section: Microplastic Extraction Protocolmentioning
confidence: 99%